Porphyry Deposits of the Canadian Cordillera - McMillian, W.; Thompson, J.; Hart, C.; Johnston, S. (Geoscience Canada, 1996)
Abstract Porphyry deposits are intrusion-related, large tonnage low grade mineral deposits with metal assemblages that may in*elude all or some of copper, molybde-num, gold and silver. The genesis of these deposits is related to the emplacement of intermediate to felsic, hypabyssal, generally porphyritic intrusions that are commonly formed at convergent plate margins. Porphyry deposits of the Canadian Cordillera occur in association with two distinctive intrusive suites: calc-alkalic and alkalic. In the Canadian Cordillera, these deposits formed during two separate time periods: Late Triassic to Middle Jurassic (early Mesozoic), and Late Cretaceous to Eocene (Mesozoic-Cenozoic). Deposits of the early Mesozoic period occur in at least three different arc terranes (Wrangellia, Stikinia and Quesnellia) with a single deposit occurring in the oceanic assemblage of the Cache Creek terrane. These terranes were located outboard from continental North America during formation of most of their contained early Mesozoic porphyry deposits. Some of the deposits of this early period may have been emplaced during terrane collisions. Metal assemblages in deposits of the calc-alkalic suite include Mo-Cu (Brenda), Cu-Mo (Highland Val-ley, Gibraltar), Cu-Mc-Au-Ag (Island Cop-per, Schaft Creek) and Cu-Au (Kemess, Kerr). The alkalic suite deposits are characterized by a Cu-Au assemblage (Copper Mountain, Afton-Ajax, Mt. Milligan, Mount Polley, Galore Creek). Although silver is recovered from calc-alkalic and alkalic porphyry copper mining operations, silver data are seldom included in the published reserve figures. Those available are in the range of 1-2 grams per tonne (g-t-1). Alkalic suite deposits are restricted to the early Mesozoic and display distinctive petrology, alteration and mineralization that suggest a similar tectonic setting for both Quesnellia and Stikinia in Early Jurassic time. The younger deposits, late Mesozoicto Cenozoic in age, formed in an intra-continental setting, after the outboard host arc and related terranes accreted to the western margin of North America. These deposits are interpreted to occur n continental arc settings, and individual deposits are hosted by a variety of older country rocks. These younger deposits also snow a spectrum of metal associations: Cu-Mo (Huckleberry, Berg), Cu-Au (-Mo) (Bell, Granisle, Fish Lake, Casino),Mo (Endako, Boss Mountain, Kit-sault,Quartz Hill), Mo-W (Logtung), Au-W (Dub-lin Gulch) and Au (Ft. Knox). There maybe a continuum between Mo, Mo-W, Au-Mo-W and Au deposits. The distribution and timing of these post-accretion deposits likely reflect major crustal structures and subduction geometry. Cordilleran porphyry metallic deposits show the full range of morphological and depth relationships found in porphyrydeposits worldwide. In addition, the Cordillera contains numerous alkalic suite deposits, which are rare worldwide: the unusual, possibly syntectonic Gibraltar deposit; and end-member gold-richgranite-hosted deposits, such as Ft. Knox (Alaska).